Rockfall at Proglacial Rockwalls-A Case Study from the Kaunertal, Austria - Vehling, Lucas; Rohn, Joachim; Moser, Michael (Geomorphology of Proglacial Systems: Landform and Sediment Dynamics in Recently Deglaciated Alpine Landscapes, 2019)
Since the Little Ice Age, high alpine regions have faced rapid glacier melting that has contributed to enhanced rockfall activity at recently deglaciated rockwalls. At the Gepatschferner, Kaunertal (Austria), rockfall activity has been quantified for the past several years using rockfall collector nets, `natural' rockfall traps and multi-temporal LiDAR. Toppling and sliding activity of large unstable rock blocks, considered as precursors of rockfalls, were monitored by steel tape measurements and electrical crackmeters. The highest rockfall activity was measured at recently deglaciated rockwalls with low rock mass quality, where rockwall back-weathering rates locally exceeded 10 mm/a. Those rates are among the highest ever published. 108 mid- and high-magnitude rockfalls with volumes between 100 and 30,000 m(3) were released between 2006 and 2012. Their scars are clustered in the proglacial high-altitude parts of the Kaunertal. As well, rockwall activity was concentrated in the autumn and winter months.
CRIS-Team WoS Importer:2021-10-18